Towards Universal Health Coverage in Uganda: A Multi-Sectoral Approach - National Planning Authority (National Planning Authority, 2019)
Globally, a country is said to have attained UHC when it is able to provide essential health services in financial protection to more than 90 percent of its population through a combination of compulsory insurance and tax revenues. In line with the global aspiration, Uganda’s UHC goal is to “provide access to essential quality health and related financial services without financial constraints to at least 65 percent of all people in Uganda by 2030